Pembuatan Website Kelompok Maduma Tani - Asido Saragih; Samuel Sibuea; Fritz Marpaung; Lawy Xenna; Tegar Arifin; Rudy Chandra; Asido Saragih (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
Sipituhuta Village is one of the villages in Pollung District which has commodities in the agricultural sector. In 2016 a farmer group called the Maduma Tani Group was established as a means for sustainable agriculture to increase income. This farmer group provides farming tools that can be borrowed by farmers. However, the lack of information about the availability of farming tools and education on agricultural processing causes the process of borrowing tools and seeking agricultural processing education is still manual. The use of the website is one of the solutions in the field of information technology that helps increase farmers' knowledge in solving agricultural problems they face and borrowing farming tools in Sipituhuta Village. The development of this website uses the prototyping method, where this method is very suitable for building small-scale and customized websites that are created based on certain requests and needs. Website development using the PHP programming language, Laravel framework, and MySQL Database Management System (DBMS). Some of the features that have been successfully developed include lending tools, viewing history of tool lending, viewing education, viewing farming projects, viewing notifications. The result of this activity is that farmers in Sipituhuta Village can easily find information about agriculture and borrow farming tools. Website testing is done using the black box method. The test results show that the website that was built has been successfully running according to its function.